AAGBS annual report 2021: at a glance (Doctor of Business Administration) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
This Doctor of Business Administration (DBA) program brings together future industry leaders and is designed to provide a learning experience for professionals who aspire to pursue postgraduate qualification.